IMPLEMENTASI PEMBELAJARAN BLENDED LEARNING TERHADAP KEMANDIRIAN BELAJAR MAHASISWA DI LINGKUNGAN UNIVERSITAS PGRI WIRANEGARA - Al Farisi, Salman; Laili, Innayatul; Damayanti, Ayu Maya; Febriyanti, Dian (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to determine the implementation of blended learning and its impact on student learning independence at PGRI Wiranegara University. The study used a quantitative approach with a descriptive correlational design. Data were obtained through questionnaires administered to students from several study programs and then analyzed descriptively using percentages. The results indicate that the implementation of blended learning provided a positive learning experience. Most students felt more active in seeking out material, less reliant on lecturers' explanations, and more responsible in completing assignments. The flexibility of time and easy access to materials through the LMS, modules, and learning videos helped students manage their study time more independently. However, challenges remained, including limited internet connection and lack of motivation during online learning. It can be concluded that blended learning is quite effective in fostering student learning independence, but it needs to be supported by adequate infrastructure and a more engaging digital learning design for optimal results.